Optimalisasi Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) dalam Meningkatkan Perekonomian Masyarakat (Studi pada UMKM di Desa Tamansuruh Banyuwangi) - Muh. Khoiruddin (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to identify the problems faced and develop strategies for developing UMKM as a form of optimization in improving the economy in Tamansuruh Village Banyuwangi. This research method uses a descriptive qualitative approach. Data collection techniques used are observation, interviews and documentation. Data analysis used interactive analysis consisting of reducing data, presenting data and drawing conclusions. The results of this study indicate that in general the problems faced by MSME actors in Tamansuruh Village include capital, marketing, human resources, facilities and infrastructure, the introduction of information technology, so that UMKM in Tamansuruh Village have not been able to run optimally. the strategies obtained are minimizing financing, considering the risks of the decisions made and conducting professional recruitment.